Targeted transscleral laser photocoagulation of the ciliary body in patients with neovascular glaucoma - Zadorozhnyy O.; Guzun, O.; Kustryn T.; Nasinnyk I.; Chechin P.; Korol A. (Ukrainian Society of Ophthalmologists, 2019)
Transscleral laser photocoagulation of the ciliary body is used to reduce intraocular pressure (IOP) in neovascular glaucoma, which is associated with a risk of complications. Purpose. To study the efficacy and safety of transscleral laser cyclophotocoagulation in patients with neovascular glaucoma using infrared transillumination to visualize the structures of the ciliary body. Material and Methods. The study included 45 patients (45 eyes) with end- stage neovascular glaucoma. All patients underwent transpalpebral infrared transillumination of the ciliary body in order to accurately position a laser probe during transscleral contact-compression 1064-nm laser cyclophotocoagulation. The follow-up period after the initial treatment was 12 months with monthly control. Results. After 12 months, the mean IOP decreased from 37.7±3.2 to 23.8±5.1 mm Hg (p=0.000). IOP normalization was achieved in 37 patients (82%). The mean number of treatment sessions was 1.8±0.6. During the 12 months follow-up there were no cases of hypotony and phthisis. Conclusion. Infrared transillumination allows imaging of ciliary body structures for targeted positioning a laser probe during transscleral laser cyclophotocoagulation. Targeted transscleral laser 1064-nm cyclophotocoagulation is an effective and safe treatment for patients with neovascular glaucoma.